PENYERAPAN FONOLOGI BAHASA SANSKERTA DALAM TEKS ADIPARWA - Putu Eka Sura Adnyana (UHN IGB Sugriwa Denpasar, 2022)
Acculturation of Indian culture with the archipelago has occurred in the past. Old Javanese language is a very important language in the development of literary works in the archipelago. Kawi language is very much absorbed from Sanskrit, but Kawi language does not imitate Sanskrit grammar. One of them is the absorption of sound or Sanskrit phonology which can be found in the Adiparwa text. The type of research carried out is qualitative research based on data in the Adiparwa text using research methods and techniques. Data collection techniques based on literature study on Adiparwa text, note-taking techniques, through qualitative data analysis. Such data from the literature is then analyzed and presented descriptively. The data is taken from the abbreviated Adiparwa Zoetmulder (2005) text (APZ) and the abbreviated Sankerta Dictionary (KBS). Language contact between Sanskrit and Old Javanese/Kawi which resulted in the sound absorption process. Sound absorption includes 1) Sanskrit absorption experiencing an increase in sound, 2) Sanskrit absorption experiencing a reduction in sound 3) Sanskrit absorption experiencing a change in sound symbolization. In the absorption of Sanskrit on sound changes, it is known that several changes were found, such as: 1) Changes in the sound symbol /v/ to /w/ and changes in the symbol /ṛ/ to /rè/. 2) Change the sound /u/ to /o/ or vice versa. 3) Change the sound /j/ to sound /k/. 4) Change the sound /i/ to /ī/. 5) Change the sound /ī/ to /i/ and 6) Change the sound /a/ to /ā/.